IPTEKS BAGI MASYARAKAT (IBM) APLIKASI DAN PELATIHAN PENGOLAHAN UNTUK MEMPEROLEH AIR BERSIH SECARA SEDERHANA MELALUI UPAYA PEMBERDAYAAN MASYARAKAT PESISIR DI SUNGAILIAT, KABUPATEN BANGKA - Henny Helmi; Umroh Umroh; Suci Puspita Sari (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2014)
People in the area of Kampung Nelayan I and II, Pesisir Sungailiat in their daily lives use water from dug wells obtained from dug wells that is yellow, tastes, smells fishy, causes brown and yellowish stains on white clothes. The water from the household's dug well does not comply with clean water quality standards and can interfere with their health. The main objective of this activity is to provide training on filtering murky water into clean water for communities experiencing a clean water crisis with a simple multilevel filter method and build two sample units of water treatment plants. The implementation of this activity involved two partners as the main supporters of the implementation of clean water facilities, namely the Fishermen I and Fishermen II groups. The training on filtering murky water from dug wells into clean water using the Simple Multilevel Filter method in fishermen areas has been carried out together with coastal communities and students so that after the training, the knowledge can be applied directly. Two sample water installation units have been built in Nelayan I and Nelayan II Villages, as an example so that the community will be able to make water treatment units independently. This activity produces a simple, safe, cheap and natural method to produce clean water that can be used by coastal communities. Two units of water installation buildings have been used by the community and the community has also been given training on how to care for and maintain filtration buildings. Public awareness on how to live a healthy life has been carried out to improve the quality of life of the Kampung Nelayan community.